Murray J. Harris, Prepositions and Theology in the Greek New Testament. An Essential Reference Resource for Exegesis (Grand Rapids, MI: Zordevan 2012) - Piwowar, Andrzej (The Biblical Annals, 2018)
Book review: Murray J. Harris, Prepositions and Theology in the Greek New Testament. An Essential Reference Resource for Exegesis (Grand Rapids, MI: Zordevan 2012). Pp. 293. 42.99. ISBN 978-0-310-49392-1 DOI: https://doi.org/10.31743/ba.2018.8.2.05